Analisis Isi Komunikasi Publik Badan Meteorologi, Klimatologi dan Geofisika (BMKG) Terkait Prakiraan Cuaca Melalui Postingan Instagram @infobmkg - Syafruddin Pohan; Misiyem Misiyem; Sarah Bonova Sinaga (STIKes Ibnu Sina Ajibarang, 2023)
The phenomenon of climate change often occurs in certain seasons, causing cyclical changes in climate conditions in an area. Climate change causes the biggest impact is global warming which causes ice and icebergs in polar regions to melt. In addition, this phenomenon also causes storms, extreme weather and changes in rainfall patterns. Through the Meteorology, Climatology and Geophysics Agency always provides information related to authentic weather forecasts through a series of public communication activities through @infobmkg Instagram posts. The purpose of this study is to analyze the content of public communication related to weather forecasts through @infobmkg Instagram posts. The research method uses a content analysis approach to describe the content of posts by analyzing them. The results of the study show that BMKG actively posts weather forecast information that is useful for the community. The information received by the community can be used as a reference for indoor or outdoor activities and always be alert to potential storms caused by bad weather.